2016
DOI: 10.1080/19768354.2016.1262896
|View full text |Cite
|
Sign up to set email alerts
|

The differentiation of cellular structure during encystment in the soil hypotrichous ciliateAustralocirruscf.australis(Protista, Ciliophora)

Abstract: Ciliates are able to form resting cysts as a survival strategy in response to stressful environmental factors. Studies on the characteristics of cellular structure during encystment may provide useful information for further understanding of the regulatory mechanism of cellular patterns and supply new clues regarding the phylogeny of ciliates. Scanning and transmission electron microscopies were used to observe the ultrastructure of cells during encystment of the soil ciliate Australocirrus cf. australis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
(40 reference statements)
0
20
0
Order By: Relevance
“…Similarly, unlike most other oxytrichids (Berger, ; Blatterer & Foissner, ; Kumar & Foissner, ), the two macronuclear nodules of Australocirrus cf. australis and Australocirrus shii did not fuse during encystment either (Kumar & Foissner, ; Li et al, ). These exceptions indicated that the behavior of macronuclear nodules is not concordant among the NKR‐ and KR‐ type of cysts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, unlike most other oxytrichids (Berger, ; Blatterer & Foissner, ; Kumar & Foissner, ), the two macronuclear nodules of Australocirrus cf. australis and Australocirrus shii did not fuse during encystment either (Kumar & Foissner, ; Li et al, ). These exceptions indicated that the behavior of macronuclear nodules is not concordant among the NKR‐ and KR‐ type of cysts.…”
Section: Discussionmentioning
confidence: 99%
“…When environmental conditions are suitable again, excystment occurs, and they return to an active state (Delgado, Calvo, & Torres, ; Grisvard, Lemullois, Morin, & Baroin‐Tourancheau, ; Pomajbíková et al, ; Rios, Sarmiento, Torres, & Fedriani, ; Tadao & Fumikazu, ). During encystment, somatic ciliature and microtubular organelles dedifferentiate; tubulin gene expression may also be decreased due to the decline in demand; the cyst walls gradually form; the shape of the macronucleus is often changed, along with chromatin condensation; and autophagic activity occurs in cytoplasmic organelles, namely, lysosomes and autophagic vesicles (Aslan, Küçükoğlu, & Arslanyolu, ; Cavaleiro, Fernandes, Silva‐Neto, & Soares, ; Li et al, ; Slabodnick et al, ; Wang et al, ; Wang, Wu, Fan, & Gu, ). During excystment, the ciliature is regenerated or reactivated, often with the activation of an excystment vacuole; certain genes and proteins related to initiating the excystment process and reconstructing the vegetative cell structure are upregulated (Funadani, Suetomo, & Matsuoka, ; Grisvard et al, ; Müller, ; Sogame et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to new study by Li et al (2017), the ectocyst morphology of oxytrichids exhibits two different types of cyst surface, that is a spine-like protuberances (e.g. Rigidohymena tetracirrata, Laurentiella acuminata, Steinia sphagnicola, Oxytricha bifaria and others) or a slightly wrinkled surface of resting cyst (Gastrostyla steinii, Australocirrus cf.…”
Section: Resting Cysts Of a Soil Ciliate 87mentioning
confidence: 99%
“…by Berger (1999), Australocirrus cf. australis by Li et al (2017), Histriculus similis [now accepted as Sterkiella quadrinucleatus (Sick, 1933) Berger, 1999 by Calvo et al (1983), Calvo et al (1986) and others. In comparison with different taxonomic group of ciliates, e.g.…”
Section: Resting Cysts Of a Soil Ciliate 87mentioning
confidence: 99%